THE BARRIERS OF PERFORMANCE OF SMALL AND MEDIUM-SIZED ENTERPRISES IN POLAND (Research Bulletins of the Faculty of Economic Sciences, 2021)
The contents of the article touches the problem of barriers to development of the sector of small and medium –sized enterprises in Poland. The identification of bariers can be made on the basis of economic books and reports. Thera are economic, legal, administrative, educational and management barriers. The limitation these main barriers can help to develop of small and medium-sized enterprises in Poland.
Keywords: barriers, enterprise, entrepreneurship, SME sektor, development